0130 Using fully immersive simulation to identify latent errors in a new major trauma centre. (2nd November 2015) - Jones, Clinton; Murphy, Mark; Welfare, Emma; Mercer, Simon
Abstract : Background/context: Simulation in-situ is gaining popularity 1 and is recognised as a method of identifying latent errors in the clinical setting to improve patient safety. 2 We have previous local experience of using in-situ simulation in the operating theatre to identify latent errors. 3 Aintree University Hospital is part of the Major Trauma Collaboration in Liverpool and is due to open a new Major Trauma Unit in the summer of 2015. We plan to use in-situ simulation to test the facility prior to opening and wish to present the outcomes of our study. Methodology (used or planned): Using the wireless mannequin SimMan 3G (Kent, UK) we intend to run the following fully immersive scenarios to involve the actual teams on call. Trauma Call Deteriorating Patient in the Resuscitation Bay Medical Emergency Team Call to Observation Ward Scenarios will be video recorded to allow an immediate debrief and a report will be written to allow any latent errors to be corrected prior to opening the facility Results/outcomes (anticipated or recorded to date): Previous work by Wheeler and colleagues 2 identified latent errors in the categories of medication, equipment and systems and resources. We will seek to identify any latent errors and correct them immediately. Potential impact: This exercise will allow rehearsal of complex trauma scenarios in a safe environment and the opportunity to correct any latent errors prior to opening our new facility. References: Mercer SJ, Wimlett S. Simulation in situ. Bull Royal College Anaesthetists 2012;76:28–30 Wheeler DS, Geis G, Mack EH, et al . High-reliability emergency response teams in the hospital: improving quality and safety using in situ simulation training. BMJ Qual Saf 2013;22:507–514 Welfare E, Lacasia-Purroy C, Groom P, et al . Investing latent errors in the operating theatre using high fidelity simulation. BMJ J Simulation Technol Enhanced Learn 2014;99 (S1):A67–68 [10.1136/bmjstel-2014-ASPiH_abstract.163]